PERLINDUNGAN HUKUM TERHADAP MEREK TERKENAL BERDASARKAN UNDANG-UNDANG MEREK DI INDONESIA - , Wenny Oktavina, Prof. M. Hawin, S.H., LL.M., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Research concerning Legal Protection Of Trademark Law on Famous Brand in Indonesia is a research of law having the character of empirical normative, which cover research to principle of justices, comparison of law, factors and elements related to Legal Protection Of Trademark Law on Famous Brand in Indonesia. This research aim to know arrangement of protection to famous brands in Law of No. 15 Year 2001 About Brand and also governmental effort of Indonesia in overcoming forgery of famous brand. This research is based on research of bibliography, and research of field to see the practice of protection of trademark law to famous brand. obtained data of research of field and research of bibliography will be analysed qualitative to is then compiled systematically. Arrangement of protection of trademark law of famous brand peculiarly not yet in arranging in Law of No. 15 Year 2001 About Brand. In the rules and regulations only giving protection of brand enlist that good of trademark, service brand and collective brand, which the included in ordinary brand, famous brand and celebrated brand. This matter do not make famous brand do not protect, but the existence of an special rule of famous brand not yet isn't it in Law of No. 15 Year 2001. Besides, conducted by effort government of Indonesia in overcoming forgery of gone through famous brand by 2 step that is with effort of preventive as preventive effort early which divided of law factor, Directorate Generals government officer factor, and technological utilization factor, and also strive repressive in the case of have happened collision of brand. effort of Repressive can be conducted with existence of cancellation suing and sanction fallout to the trespasser of rights of brand.